Комунікативні стратегії в девіантній комунікації (на прикладі українськомовних медійних текстів на воєнну тематику) - Гарюнова, Ю. О.; Hariunova, Yu. O.; Єльнікова, Н. І.; Yelnikova, N. I.; ORCID: http://orcid.org/0000-0002-5061-8226 (Вчені записки ТНУ імені В. І. Вернадського. Сер.: Філологія. Журналістика. – 2022. – Т. 33 (72), № 3. - С. 12-16, 2022)
Досліджено передумови виникнення девіантної комунікації, описанои сучасні підходи в дослідженні проблеми девіації, окреслено тенденції у вирішенні проблеми її детермінування, загально розглянуто підходи вітчизняних і зарубіжних науковців різних галузей щодо проблеми девіантної поведінки. Акцентовано основні стратегії, до яких звертаються мовці-агресори в ситуації протистояння й розпалення конфлікту: провокація, дискредитація, образа. Визначено, що стратегії дискредитації може передбачати звернення до тактик дискримінації, спаплюження, ураження й приниження. Зроблено припущення, що існування третього компонента комунікації, а саме «мовчазного спостерігача», можна вважати однією з провідних умов для реалізації девіантної комунікації. Наголошено, що аксіологічний компонент становить комунікативну основу агресивного мовлення в інтернет-просторі, що передбачає звернення провокатора до оцінного лексичного компонента в прихованій чи завуальованій формі, імпліцитній чи експліцитній.

An attempt to investigate pre-conditions of origin of deviant communication, describe modern approaches in research of problem of deviation is carried out in the article, tendencies are outlined in the decision of problem of her determination, in general lines approaches of home and foreign scientists of different industries are considered in relation to the problem of deviant behavior. An attempt to investigate the situation of language opposition from the point of view of the use of basic communicative strategies and tactician is realized in a studio. The problem of definition of terms " deviant communication" is outlined and "strategy" that is most actual in the context of aggressive commonunication in internet, in particular in contexts on military subjects. Basic strategies that aggressors call in the situation of opposition and flamе conflict are accented: provocation, discredit, offense. Certainly, that strategies of discredit an appeal can envisage to tactician of discrimination, desecration, defeat and humiliation. Supposition is done, that existence of the third component of communication, namely "taciturn observer", it can consider one of leading terms for realization of deviantcommunication. Actual and meaningful is conclusionposition that the component of axiology presents communicative basis of the aggressive broadcasting in internet, that envisages the address of aggressor to the evaluation lexical component in the hidden or veiled form implicit or explicit. In case of conflict communication strategic actions of talkings are difficult enough and various, that is why there is not possibility to describe all real cases of deviantcommunication by means of one general formula or lay down the chart of her realization. The important and actual is seemed by the problem of differentiation of space of commonunication on "it" and "stranger", that does meaningful the problem of language aggression for the specialists of socio- and psycholinguistics. Deviantcommunication can not be formed and realized without expression of negative estimation of unacceptable, in opinion of talkings, element or fact of reality. Common and skilled determination of language strategy mainly depends on that, what answer in the situation of commonunication is given by discriminated personality.

Исследованы предпосылки возникновения девиантной коммуникации, описаны современные подходы в исследовании проблемы девиации, очерчены тенденции в решении проблемы ее детерминирования, рассмотрены подходы отечественных и зарубежных ученых различных отраслей относительно проблемы девиантного поведения. Акцентированы основные стратегии, к которым обращаются говорящие-агрессоры в ситуации противостояния и разжигания конфликта: провокация, дискредитация, оскорбление. Определено, что стратегия дискредитации может предусматривать обращение к тактикам дискриминации, осквернению, поражению и унижению. Предполагается, что существование третьего компонента коммуникации, а именно «молчаливого наблюдателя», можно считать одним из ведущих условий для реализации девиантной коммуникации. Отмечено, что аксиологический компонент составляет коммуникативную основу агрессивной речи в интернет-пространстве, что предполагает обращение провокатора к оценочному лексическому компоненту в скрытой или завуалированной форме, имплицитной или эксплицитной.
Communicative strategies in deviant communication (on the example of Ukrainian-language media texts on military themes)
Гарюнова, Ю. О. Комунікативні стратегії в девіантній комунікації (на прикладі українськомовних медійних текстів на воєнну тематику) / Гарюнова Ю. О., Єльнікова Н. І. // Вчені записки ТНУ імені В. І. Вернадського. Сер.: Філологія. Журналістика. – 2022. – Т. 33 (72), № 3. - С. 12-16. - DOI: https://doi.org/10.32838/2710-4656/2022.3/03.
Keywords: Мова. Мовознавство. Літературознавство. Language. Linguistics. History and Criticism of Literature. Язык. Языкознание. Литературоведение; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Психологія. Рsychology. Психология; комунікація; communication; коммуникация; комунікативна стратегія; communication strategy; коммуникативная стратегия; девіація; deviation; девиация; мовний агресор; linguistic aggressor; языковой агрессор; девіантна комунікація; deviant communication; девиантная коммуникация; дискредитація; discredit; дискредитация; девіантна поведінка; deviant behavior; девиантное поведение